IMPLEMENTING CONCEPT MAPPING TECHNIQUE TO IMPROVE STUDENTS DESCRIPTIVE WRITING ABILITY - Rubiyah, Rubiyah; Ping, Maria Teodora; Syamdianita, Syamdianita (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
This Classroom Action Research aimed at investigating the implementation of Concept Mapping Technique to improve students descriptive writing ability. The research was conducted in two cycles at SMP Negeri 21 Samarinda, with 37 seventh grade students participating. In this research, there was one teacher- researcher who implemented the technique and there were two collaborators who did the observation. The data were collected both quantitatively and qualitatively by using writing assessment, interview guide, observation sheets and field notes. The findings showed that: 1) there was an improvement in the students descriptive writing average scores at the end of the second research cycle; 2) the implementation of the concept mapping technique was done properly by the teacher- researcher; 3) the concept mapping technique delivered through collaborative working improved the participation of the students in the teaching and learning process. Since all the criteria of success in this research were fulfilled by the end of the second cycle, it could be concluded that this classroom action research was successfully implemented and the technique proposed could very well improve the skills being targeted.